Creating a collaborative learning environment online and in a blended history environment during Covid-19 (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Collaboration is key to an effective history classroom. Discussion, peer work and learner engagement facilitate the development of historical thinking skills, understanding of historical content and a careful engagement with the ethical issues posed in studying history. The realities of teaching online and then in a blended learning environment during COVID-19 have created challenges for maintaining this collaborative environment. The article discusses a number of techniques that have been employed to foster general engagement and also to scaffold assessment.
Keywords: Collaboration; COVID-19; Group work; Peer learning; Constructivist learning